Rumah Gadang Mande Rubiah South Coast of West Sumatra: Between Religious Tourism, The Museum of The Heritage of Bundo Kanduang and A Sacred Place - Ahmad Putra; Syaiful Adnan; Joni Indra Wandi; Yulia Fitria; Nora Afnita; Bayu Pramesta (Dampeng: Journal of Art, Heritage and Culture, 2025)
This research is motivated by the increasing number of tourists visiting Rumah Gadang Mande Rubiah, where Rumah Gadang Mande Rubiah is one of the real witnesses to the extraordinary struggle of the predecessors and the existence of the history of Bundo Kanduang in the past. Today, this historical witness is not just a location for religious tourism, but also stores historical relics that are still preserved to this day. In addition, it is said that there are still mystical things that are believed to still be stored and believed to exist. This means that Rumah Gadang Mande Rubiah can be said to be a sacred place so that it is interesting to trace the history stored in it. In tracing the uniqueness and important things in this study, the researcher used the library research method, where the author collected materials through journals, books, writings related to the issues discussed. The purpose of the research that the author made was to reintroduce the history of Rumah Gadang Mande Rubiah to the general public, both in the South Coast of West Sumatra and on a national scale, where Rumah Gadang Mande Rubiah stores interesting things and provides knowledge of a history that is useful to be studied again. In addition, the researcher also discussed this research with the aim of making the younger generation interested in tracing, rereading history, and seeing the struggles of their predecessors in fighting for a culture, customs and values ??of togetherness whose physical evidence can still be witnessed today. Abstrak: Penelitian ini dilatar belakangi dengan meningkatnya wisatawan yang berkunjung ke Rumah Gadang Mande Rubiah, yang mana Rumah Gadang Mande Rubiah menjadi salah satu saksi nyata akan luar biasanya perjuangan para pendahulu dan keberadaan sejarah Bundo Kanduang tempo dulu. Hari ini, saksi sejarah tersebut bukan sekedar lokasi untuk wisata religi saja, namun juga menyimpan peninggalan-peninggalan bersejarah yang masih terjaga sampai saat ini. Di samping itu, konon masih tersimpan hal-hal mistis yang dipercaya masih tersimpan dan dipercayai keberadaannya. Artinya, Rumah Gadang Mande Rubiah dapat dikatakan tempat yang sakral sehingga menarik bila menelusuri sejarah yang tersimpan di dalamnya. Dalam menelusuri keunikan dan hal penting dalam penelitian ini, peneliti menggunakan metode library research, dimana penulis mengumpulkan bahan melalui jurnal, buku-buku, tulisan-tulisan yang berkaitan dengan persoalan yang dibahas. Tujuan dari penelitian yang penulis buat ialah mengenalkan kembali sejarah Rumah Gadang Mande Rubiah kepada khalayak ramai baik yang ada di Pesisir Selatan Sumatera Barat maupun skala Nasional, di mana Rumah Gadang Mande Rubiah menyimpan hal-hal menarik dan memberikan pengetahuan akan sebuah sejarah yang bermanfaat untuk kembali dipelajari. Di samping itu, penelitian ini peneliti bahas juga bertujuan agar para generasi muda tertarik menelusuri, membaca kembali sejarah, dan melihat perjuangan para pendahulu dalam memperjuangkan sebuah budaya, adat serta nilai-nilai kebersamaan yang bukti fisiknya masih bisa disaksikan sampai hari ini. Kata Kunci: Rumah Gadang, Mande Rubiah, Sejarah